Silica coating followed by heat-treatment of MDP-primer for resin bond stability to yttria-stabilized zirconia polycrystals - Dal Piva, Amanda M. O. [UNESP]; Carvalho, Ronaldo L. A. [UNESP]; Lima, Aline L. [UNESP]; Bottino, Marco A. [UNESP]; Melo, Renata M. [UNESP]; Valandro, Luiz Felipe (Wiley, 2019)
This study evaluated the influence of silica coating, primer type and its heat treatment on bond strength durability between resin cement and an yttrium-stabilized polycrystalline tetragonal zirconia (Y-TZP). Eighty (80) Y-TZP blocks were allocated into 16 groups considering four factors: silica coating (without and with); type of primer (RelyX Ceramic Primer, a silane-based primer; Single Bond Universal, a universal MDP-based primer); heat treatment of the primer (without and with); aging (without and with). After zirconia treatments, resin cement cylinders (RelyX ARC) (n = 20; N = 320) were built. Half of the samples were tested after 24 h, and another half were subjected to aging (thermocycling 5–55°C/5.000, and storage in water for 6 months). Shear bond strength test and failure analysis were performed. Bond strength data were submitted to four-way ANOVA and Tukey test (p = 0.05). All factors were statistically significant (p < 0.001) for bond strength (MPa): silica coating (7.3 ± 5.9) > no-treatment (3.6 ± 4.3); universal primer (6.7 ± 4.8) > silane (4.2 ± 5.8); heat-treatment (6.5 ± 6.3) > no-heating (4.4 ± 4.3); no-aging (8.2 ± 5) > aging (2.7 ± 4.4). Tukey test revealed that the association of silica coating + universal primer + heat-treatment promoted higher and stable resin bond strength. Silica coating, universal adhesive application and heat treatment improve/increase durability and bond strength of zirconia. © 2018 Wiley Periodicals, Inc. J Biomed Mater Res Part B: Appl Biomater, 107B: 104–111, 2019.
Keywords: adhesion; air-abrasion; polycrystalline; tribochemical silica coating; zirconium